UZBEKISTAN IN THE GLOBAL MARKET: WHAT WILL CHANGE THROUGH MEMBERSHIP IN THE WTO (WORLD TRADE ORGANIZATION) - Baratov Diyorbek Fazliddin oglu (Ecomind Press, 2025)
This study analyzes the process of Uzbekistan's membership in the World Trade Organization (WTO) and the changes that will occur as a result of its integration with the global market. WTO membership creates new opportunities for the economy of Uzbekistan, including increasing trade freedom, attracting investments, and developing international economic relations. The study examines the main advantages of WTO membership, as well as its impact on Uzbekistan's export and import strategies. This process also contributes to the modernization of the country's domestic market, increasing competitiveness in manufacturing and services.
Keywords: WTO, antitrust, investment, integration, trade, GDP, economic growth, inflation, marginalization, export and import.